KETERLINDIAN POLUTAN LOGAM BERAT HASIL SOLIDIFIKASI/STABILISASI TAILING YANG DIMANFAATKAN SEBAGAI BACKFILLING TAMBANG BAWAH TANAH - Rara Dewi Arumsari, Raden
Tailings are disposed material after extracting valuable minerals such as gold, silver, copper, etc from an ore. In Indonesia, according to Government Regulation No. 18 jo 85/1999 tailings are categorized as hazardous waste with code D222. Tailings that are produced in large quantities are potentially pollute the environment. One common method for tailings management is its usage as backfilling material. Backfilling is a technique that refills the mine pit with tailings for ground support. Environmental issue that needs to be considered in backfilling is heavy metals leachability potential that can contaminate the groundwater. In this study, heavy metals leachability potential from backfill specimen of tailing from gold mining was analyzed in laboratory scale. The purpose of this study was to determine the heavy metals leachability pattern from material backfill. Physical and chemical characteristic tests of tailing which consist of water content, volatile content, ash content, sieve analysis, fineness modulus, specific gravity, weight volume, pH, content of heavy metals, metal oxides and the TCLP test were performed. The used methods were tailings solidification and stabilization by adding three variation composition of Portland type I cement, then compressive strength test and three kinds of leachability test (TCLP, multiple-TCLP and submerge leachability test), that were performed to the specimen. The parameters for leachability test were 11 heavy metals according to Government Regulation No. 18 jo 85/1999. TCLP results for tailing solidification showed the significant decreased of Ba and Cd concentrations, but increased for Cr and Zn concentration compare to initial tailing. Ba decreased from 3,002 mg/L to 0,118 mg/L for 3% cement, 0,075 mg/L for 4% cement, 0,082 mg/L for 5% cement and 0,066 mg/L for slurry. Cd decreased from 0,076 mg/L to 0,066 mg/L for 3% cement, 0,058 mg/L for 4% cement, 0,065 mg/L for 5% cement and 0,042 for slurry. Cr increased from 0,050 mg/L to 0,078 mg/L for 3% cement, 0,094 mg/L for 4% cement, 0,082 mg/L for 5% cement and 0,245 mg/L mg/L for slurry. Zn increased from 0,399 mg/L to 1,953 mg/L for 3% cement, 2,478 mg/L for 4% cement 2,607 mg/L for 5% cement and 3,512 mg/L for slurry. Concentration of all heavy metal leachability still complied the standard of Government Rules No 18 jo 85/1999.